Stability of switched positive linear time-delay systems - Liu, Li-Juan; Zhao, Xudong; Wu, Di (IET control theory & applications, 2019)
In this study, the authors analyse the stability of switched positive linear time-delay systems. By developing a novel multiple discontinuous co-positive Lyapunov–Krasovskii functional approach, the stability conditions are established for switched positive time delay systems by a linear programming approach under mode-dependent average dwell time switching. Moreover, under average dwell time switching, the corresponding stability conditions are also proposed. It is shown that their results can obtain smaller lower bounds on dwell time. Finally, simulation results are given to show the effectiveness of their methods.